Study on electrical characteristics of XLPE insulation of high voltage cable - Yang, Juanjuan (2009)
Polyethylene polymers, especially cross-linked polyethylene (XLPE), are widely used in high voltage transmission cables. Electrical treeing is one of the most important degradation mechanisms in aged XLPE cable system. Partial discharge (PD) technique is one of the effective methods to identify this slowly developing fault. For studying the aging mechanism, space charge accumulation and local electric field are the important parameters. Increased electrical stress is simulated by typical point-plane electrode geometry. For PD pulses distributed in 20 ms, some time-domain distributions have been analyzed, including -q, n-q, ∆u-∆t and Weibull distributions. For single PD pulses, various analyses have been carried out to study the frequency content. The effects of stress level and aging time have been compared in three test modes. Two types of electrical trees have been identified based on PD analysis and optical recording. Observed light emission supported the theory of emission by protons due to high-energy electrons. The above analyses are supported with dielectric response measurements. The needle-plane electrode configuration has been analyzed in respect of the influences of geometry parameters on the electric stress. The electric field distribution in three cases helps understand the initiation and growth of electrical trees. Considering the field- and thermal- dependent nonlinear conductivity of polyethylene, the transient distributions of electric field and space charge density are analyzed under different waveforms. Significant temperature rise occurs when a fast-rise waveform is applied. Going deeper to the macroscopic scale, Poisson’s equation, continuity equation and transport equation are combined to form a bipolar charge transport model. COMSOL® is successfully applied to solve such multiphysics problem. By assuming unique and exponential deep trapping levels, respectively, a one-dimensional (1D) problem of field and space charge density is solved for two types of computation cells. The first type is traditionally used in charge transport analyses, while the second one is specially designed for the needle-plane electrode geometry. The two assumptions are not equivalent. However, the former model is useful to explain the long time decaying and the latter one exhibits the features of field-limited space charge. To study the high frequency response of XLPE cable, the complex permittivity is an important parameter. For XLPE, a large measurement error takes place due to the fringing effect from traditional parallel-electrode system. Based on the field-circuit coupled theory, a correction curve can be acquired by assuming initial values. And the influence factors of this curve have been analyzed. The field-circuit coupled method is verified by a measurement. This method shows advantage in accuracy over the traditional guarded-electrode measurement and it has the theoretical practicability to eliminate the limit on sample dimension and electrode configuration. Since the high-permittivity semicon shows a dominant effect on high frequency loss, the dimensional effect has also been investigated and a mathematical model has been set up. Due to the electric field distortion, the dimensional effect makes the apparent complex permittivity deviate from the intrinsic value above hundreds of MHz. Moreover, when the intrinsic permittivities of both XLPE and semicon are unknown, the apparent values of permittivity could be different from the intrinsic values due to the fringing and dimensional effects. The field-circuit coupled method has been proven still applicable. The complex permittivities of XLPE and semicon can be iteratively derived from the measurement results by using Newton-Raphson method.